2022
DOI: 10.1155/2022/6951532
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Video Target Detection and Tracking in Football Matches

Abstract: Computer vision is an interesting branch of artificial intelligence which is dedicated to how electronic devices can achieve the level of capabilities to perceive things just like ordinary human beings do. In order to solve the poor effect of video for the detection of target in football matches and the low accuracy of target tracking, this paper aims to make a deep exploration of the methods of video for the detection of target and tracking in football matches. The video moving for the detection of target met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…During the COVID-19 pandemic, the clusters in the topic area were reduced, and only one topic was clustered with keywords that had different meanings than before the pandemic. The only independent cluster of keywords in the technology topic area during the pandemic was found in the soccer area that discussed advanced AI movement-tracking technology ( Jin, 2022 ; Zou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the clusters in the topic area were reduced, and only one topic was clustered with keywords that had different meanings than before the pandemic. The only independent cluster of keywords in the technology topic area during the pandemic was found in the soccer area that discussed advanced AI movement-tracking technology ( Jin, 2022 ; Zou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%